2002
DOI: 10.1034/j.1600-079x.2002.1844.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intracellular calcium and calmodulin by melatonin in MCF‐7 human breast cancer cells

Abstract: The pineal hormone, melatonin, has been shown to inhibit the proliferation of the estrogen receptor alpha (ERalpha)-positive macrophage chemotactic factor (MCF)-7 human breast cancer cells. Previous studies from other systems indicate that melatonin modulates the calcium (Ca2+)/calmodulin (CaM) signaling pathway either by changing intracellular calcium concentration ([Ca2+]i) via activation of its G-protein coupled membrane receptors, or through a direct interaction with CaM. In this study, although melatonin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 45 publications
4
45
0
1
Order By: Relevance
“…Given the importance of the caveoli to various signaling pathways, including the membrane ERa (mERa), it is possible that melatonin, via activation of its MT1 receptor, can impact the signaling of a number of important pathways including those modulated by the membrane ERa. In fact, we have previously reported [3] that melatonin can significantly blunt E2's non-genomic induction of cAMP in MCF-7 human breast cancer cells [3] and can alter Calmodulin subcellular distribution within human breast cancer cells [31]. Thus, the ability of melatonin to modulate E2's non-genomic effects may be mediated through interactions with the membrane ER (ERa or GPCR30) signaling pathway(s) within the caveoli.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of the caveoli to various signaling pathways, including the membrane ERa (mERa), it is possible that melatonin, via activation of its MT1 receptor, can impact the signaling of a number of important pathways including those modulated by the membrane ERa. In fact, we have previously reported [3] that melatonin can significantly blunt E2's non-genomic induction of cAMP in MCF-7 human breast cancer cells [3] and can alter Calmodulin subcellular distribution within human breast cancer cells [31]. Thus, the ability of melatonin to modulate E2's non-genomic effects may be mediated through interactions with the membrane ER (ERa or GPCR30) signaling pathway(s) within the caveoli.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that these findings may help in the design of therapeutic strategies against lethal reperfusion injury, with Na π /Ca ππ exchange as the target (Inserte et al 2002). There are reports about melatonin improving Ca ππ signaling in dysfunctional endothelial cells (Pogan et al 2002), elevation of cytosolic Ca ππ levels in MCF-7 human breast cancer cells (Dai et al 2002). In a recent article of melatonin receptors was shown to be present in human cardiovascular system, thus postulating that putative receptor-mediated effects of melatonin on cardiac myocytes may be a result (Ekmekcioglu et al 2003).…”
Section: Carbon Monoxide Cardiotoxicitymentioning
confidence: 99%
“…Some of these compounds used as pharmacological agents to block CaM-mediated enzyme activation may act as antipsychotics, muscle relaxants, antidepressants, minor tranquilizers, and local anesthetics Zhang et al 1990). CaM antagonists (such as trifluoperazine [TFP] and many others) are also being evaluated for the treatment of cancers that are both sensitive and resistant to conventional anticancer drugs (Ford and Hait 1990;Liu et al 2002), because diseases characterized by unregulated cell growth have been shown to present elevated levels of Ca 2+ -CaM (Hickie et al 1983;Dai et al 2002).…”
mentioning
confidence: 99%
“…In other cancer cell types, melatonin, either alone or in combination with other agents, induces apoptotic cell death (Blask et al 2002). Melatonin/CaM interactions may play an important role in mediating the growth-inhibitory effect of melatonin on human breast cancer cells (Dai et al 2002). Despite its pharmacological and physiological significance, a structural characterization of the CaM/melatonin interaction is still lacking, and even the strength of the interaction remains controversial (Benitez-King et al 1996; Ouyang and Vogel 1998).…”
mentioning
confidence: 99%